Effects of boom and bust grazing management on vegetation and health of beef cattle used for wildfire prevention in a Mediterranean forest - Teruel-Coll M. (2019)
This project and manuscript were partially supported by Universidad Autonóma de Barcelona (UAB), Spanish Ministerio de Economia y Competitividad (MINECO) through a Ramon y Cajal agreement (RYC-2016-21120), Cienciactiva-CONCYTEC (concession contract number 236-2015-FONDECYT), and the Life project “LIFE13 BIO/ES/000094”. Our thanks also to Andreu Colom, María Puig, Santiago Lavín, and “El Brunet” farm for their collaboration in laboratory and field works.